Understanding gender and age differences in language use: cross-cultural insights from Weibo and Facebook - Pang, Dandan; Guntuku, Sharath Chandra; Sherman, Garrick; Liu, Tingting; Rai, Sunny; Cho, Young-Min; You, Rian; Bakker, Arnold B.; Ungar, Lyle H. (Springer, 2025)
This study integrates social role theory and socioemotional selectivity theory to investigate the cultural universalities and differences in language use among male and female users across different age groups on Weibo and Facebook. By analyzing social media language, we aim to understand how gender and age influence linguistic patterns and reflect broader cultural norms and societal values. Aggregated language from Weibo and Facebook users (N = 8728 per platform; 665,377 and 742,418 posts, respectively) was analyzed by both a top-down closed-vocabulary (Linguistic Inquiry and Word Count) approach and a data-driven open-vocabulary (Differential Language Analysis) approach. Our findings support and extend social role theory, showing that female users on both platforms use more communal and relational language, while male users focus on agentic and task-oriented content. Cultural dimensions, such as collectivism and individualism, modulate the expression of social roles, with Weibo users adhering more closely to traditional gender norms compared to Facebook users. Our findings also validate and extend the socioemotional selectivity theory by demonstrating how cultural frameworks shape the specific ways aging individuals pursue emotional and social goals. For example, on both platforms, age-related language patterns reveal a U-shaped trend in positive emotions, with a decline in middle age and an increase in older adulthood, reflecting a universal shift toward emotionally meaningful goals. Additionally, older users on Weibo engage more in collectivistic themes, while their Facebook counterparts focus on personal well-being and social ties. These results highlight the complex interplay between culture, gender, and age in shaping language use on social media, providing valuable insights into the cultural and societal influences on communication.
Keywords: fi=Henkilöstöjohtaminen|en=Human Resource Management|